The Albanian question reshaping the Balkans - Pettifer, James; Vickers, Miranda (I.B. Tauris, 2007)
In 1997 the previously little-known and isolated Balkan country of Albania exploded as the first armed uprising in mainland Europe since the 1920s brought the country to the brink of civil war. As the violence spread first to neighbouring Kosovo, then to south-east Serbia and finally to former Yugoslav Macedonia, the Albanian question increasingly took center stage in world affairs. This book examines Albania's place in the Balkans, a region which had been forced simultaneously to come to terms with the realities of a post-Communist world and the threat of Slobodan Milosevic's ""Greater Serbia"" project.